Pengaruh Likuiditas, Leverage, Profitabilitas Terhadap Financial Distress - Ade Kurniawan Sofyan; Mahroji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial Distress describes a significant and continuous decline in a company's financial performance which, if left unchecked, will result in bankruptcy. The main objective of this research is to determine the effect of liquidity, leverage and profitability on financial distress. This research was conducted on property and real estate companies for the 2021–2023 period. A total of 73 companies were selected as samples in collecting data for this research. The relationship between the dependent variable and the independent variables was analyzed using logistic regression. The results of the analysis show that liquidity and profitability have a significant effect on financial distress in a negative direction, while leverage has a significant effect on financial distress in a positive direction. It is hoped that future research can expand the research object and compare various measurement techniques to provide a more comprehensive picture. It is hoped that the results of this research will be useful for stakeholders, especially creditors and investors, in making decisions regarding funding and investment.